3D printing of ceramics: A review. Issue 4 (April 2019) - Chen, Zhangwei; Li, Ziyong; Li, Junjie; Liu, Chengbo; Lao, Changshi; Fu, Yuelong; Liu, Changyong; Li, Yang; Wang, Pei; He, Yi
Abstract: Along with extensive research on the three-dimensional (3D) printing of polymers and metals, 3D printing of ceramics is now the latest trend to come under the spotlight. The ability to fabricate ceramic components of arbitrarily complex shapes has been extremely challenging without 3D printing. This review focuses on the latest advances in the 3D printing of ceramics and presents the historical origins and evolution of each related technique. The main technical aspects, including feedstock properties, process control, post-treatments and energy source–material interactions, are also discussed. The technical challenges and advice about how to address these are presented. Comparisons are made between the techniques to facilitate the selection of the best ones in practical use. In addition, representative applications of the 3D printing of various types of ceramics are surveyed. Future directions are pointed out on the advancement on materials and forming mechanism for the fabrication of high-performance ceramic components.